L‐arginine stimulates the proliferation of mouse mammary epithelial cells and the development of mammary gland in pubertal mice by activating the GPRC6A/PI3K/AKT/mTOR signalling pathway. Issue 6 (26th May 2022) - Ge, Yusong; Li, Feng; He, Yuan; Cao, Yu; Guo, Wenjin; Hu, Guiqiu; Liu, Juxiong; Fu, Shoupeng
Abstract: Amino acids have been shown to affect the development of mammary gland (MG). However, it is unclear whether L‐arginine promotes the development of pubertal MG. Therefore, our study aims to explore the effect of L‐arginine on the development of MG in pubertal mice. To investigate its internal mechanism of action, we will use mouse mammary epithelial cells (mMECs) line. Whole‐mount staining showed that L‐arginine can promote the extension of MG duct. In vitro, 0.4 mM L‐arginine could activate the G protein‐coupled receptor family C, group 6, subtype A (GPRC6A)/phosphoinositide 3‐kinase (PI3K)/protein kinase B (AKT)/mammalian target of rapamycin (mTOR) signalling pathway and increase the phosphorylation of eukaryotic initiation factor 4E binding protein 1 (4EBP1) to promote the synthesis of cell cycle regulatory protein D1 (Cyclin D1), leading to the dissociation of the retinoblastoma tumour suppressor protein (Rb)‐E2F1 transcription factor (E2F1) complex in mMECs and releasing E2F1 to promote cell proliferation. Furthermore, GPRC6A was knocked down or inhibition of the PI3K/AKT/mTOR signalling pathway with corresponding inhibitors completely abolished the arginine‐induced promotion of mMECs proliferation. In vivo, it was further confirmed that 0.1% L‐arginine can activate the PI3K/AKT/mTOR signalling pathway in the MG of pubertal mice. These results were able to indicate that L‐arginine stimulates the development of MG in pubertal mice through the GPRC6A/PI3K/AKT/mTOR signalling pathway.